PENGARUH KREATIVITAS BELAJAR DAN GAYA BELAJAR VISUAL TERHADAP HASIL BELAJAR SISWA KELAS IV SDN KESEMEN - Izah Fauziah; Shella Adellia Yesriani; Desty Endrawati Subroto (Jurnal Padamu Negeri, 2024)
Learning creativity is influenced by several factors including interest, learning concentration, learning motivation, learning habits, learning style. At Kesemen Elementary School, student learning outcomes are classified as low, which is thought to be influenced by learning creativity factors and visual learning styles, as proven by observation results such as students not listening to the teacher's explanations, many students still lack enthusiasm in receiving learning, students are less able to give opinions in answering questions. given by the teacher in class, students lack creativity in developing new ideas in the learning process, lack of listening to the teacher's explanations during learning. Apart from that, students are found unable to sit still in the learning process. This type of research is correlational. The population in this study was 63 students. The sample in this study used a total sampling technique totaling 63 people. The data collection technique used was a questionnaire. Before the questionnaire was distributed to research respondents, a trial was first carried out with the aim of measuring the validity and reliability of the statements. The data analysis techniques used are descriptive data analysis, analysis prerequisite tests consisting of normality and homogeneity tests, multiple linear regression analysis tests, coefficient of determination and hypothesis testing. The tool used to test all of this is SPSS version 18.0. Based on the results of data analysis, it was found that there was a significant positive influence between learning creativity (X1) on learning outcomes (Y). For the learning creativity variable, the t-count value was 2.862 > t table of 1.670 with a significant value of 0.006 < 0.05.  Furthermore, it was also found that there was a significant influence between visual learning style (X2) on learning outcomes (Y). For the learning style variable, the tcount value was 2.254 > ttable of 1.760 with a significant value of 0.028 < = 0.05 and there was an influence of learning creativity and visual learning style on student learning outcomes together of 2.178 with a determinant result of 0.191. This means that learning creativity (X1) and visual learning style (X2) influence the learning outcome variable (Y) by 19.1%, the remaining 81.9% is influenced by other factors not included in this research. So a multiple linear regression can be formulated Y = 25,651+ 0.276X1 + 0.250X2. Apart from that, the analysis results found a TCR of 77.48%. The highest level of achievement for respondents was in the learning creativity variable with tcr, which was 80.5%. while the lowest is in the visual learning style variable with tcr which is 74.46%